Contrasting Health Literacy in Physical Activities: A Study Across Various Academic Stages in Exercise and Sport Science Students - Julavanichpong, Tanida; Hanmanop, Kittipob; Huan-Kim, Thanakorn; Maneejak, Thiranat; Namthongton, Napas; Suwatthanapiriy, Veerapat; Sucharit, Satanachan; Singhnoi, Chatkamon; Choosakul, Chairat (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
This research aimed to assess health literacy regarding physical activities among Exercise and Sports Science students across different academic years. Involving 194 students selected via simple random sampling from Burapha University, the study utilised a comprehensive questionnaire A pivotal instrument in this methodology was the "Health Literacy in Physical Activities for Adolescents" questionnaire, adapted from Khunkitti's 2020 work and conceptually based on Pander, Murdaugh, and Parsons (2011) work to evaluate various aspects of physical activity literacy, including knowledge, access, opinions, and engagement. The questionnaire demonstrated a reliability score of .85. Statistical methods such as ANOVA were employed for analysis. The findings indicated uniformly high levels of health literacy across all academic years in areas like knowledge and perception of physical activities, with moderate engagement in actual physical activities. No significant variances were observed between different academic years regarding understanding, accessibility, opinions, family and community involvement, and physical activity practices among students.